2019
DOI: 10.1002/zaac.201900018
|View full text |Cite
|
Sign up to set email alerts
|

Metal Chelate Monomers Based on Nickel Maleate and Chelating N‐Heterocycles as Precursors of Core‐shell Nanomaterials with Advanced Tribological Properties

Abstract: In this study, new metal chelate monomers based on nickel(II) maleate and chelating N‐heterocycles (2,2′‐bipyridine and 1,10‐phenanthroline) were synthesized and characterized. A detailed analysis of the main stages and features of the kinetics of thermal transformations of metal chelate monomers was carried out. Core‐shell nanomaterials containing nanoparticles of nickel oxide and metallic nickel in a stabilizing nitrogen‐containing polymer matrix were obtained by thermolysis of these monomers. The compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In recent years, a direction based on the preparation of metal-containing monomers (MCMs) with terpyridine fragments and metallocopolymers based on them, which have self-healing properties, has been intensively developed [180][181][182]. A series of mixed-ligand complexes based on unsaturated carboxylic acids (maleic, acrylic, β-phenylacrylic, and itaconic), as well as cobalt(II) [183], nickel(II) [184,185], copper(II), and zinc(II) [186,187] ions were obtained by the interaction of metal-containing monomers with 4-phenyl-2,2 :6 ,2terpyridine (Figure 17). MCMs of this type are of interest from the point of view of the presence of M-L coordination bonds and the stereochemistry of the chelate site, as well as because of the effect of the metal ion on the reactivity of the double bond during polymerization and the possibility of creating a wide range of polymer architectures, including metallosupramolecular polymers with self-healing properties.…”
Section: With Terpyridine Ligandsmentioning
confidence: 99%
“…In recent years, a direction based on the preparation of metal-containing monomers (MCMs) with terpyridine fragments and metallocopolymers based on them, which have self-healing properties, has been intensively developed [180][181][182]. A series of mixed-ligand complexes based on unsaturated carboxylic acids (maleic, acrylic, β-phenylacrylic, and itaconic), as well as cobalt(II) [183], nickel(II) [184,185], copper(II), and zinc(II) [186,187] ions were obtained by the interaction of metal-containing monomers with 4-phenyl-2,2 :6 ,2terpyridine (Figure 17). MCMs of this type are of interest from the point of view of the presence of M-L coordination bonds and the stereochemistry of the chelate site, as well as because of the effect of the metal ion on the reactivity of the double bond during polymerization and the possibility of creating a wide range of polymer architectures, including metallosupramolecular polymers with self-healing properties.…”
Section: With Terpyridine Ligandsmentioning
confidence: 99%
“…We have previously shown [28–35] that the nature of the precursor has a significant impact on the main characteristics of the resulting nanomaterials. In particular, the introduction of long‐chain hydrocarbon radicals into precursor molecules helps stabilize NPs and prevents their aggregation [36] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nitrogen-metal-carbon (NMC) NPs obtained by thermolysis of precursors containing these elements have received wide attention due to their natural content, economic attractiveness and extended functionality. [23][24][25][26][27][28][29] Previous studies have shown that the activity of NÀ MÀ C catalysts largely correlates with the properties of precursors, thermolysis conditions, type of carbon, content of elements, etc. [30] Recently, Zhou et al synthesized an Fe/N co-doped graphitic carbon bulb with a high nitrogen content by pyrolysis of a Prussian blue precursor at a low temperature of 550°C.…”
Section: Introductionmentioning
confidence: 99%